2023
DOI: 10.3389/fpls.2023.1272335
|View full text |Cite
|
Sign up to set email alerts
|

The cotton charcoal rot causal agent, Macrophomina phaseolina, biological and chemical control

Ofir Degani,
Asaf Gordani,
Elhanan Dimant
et al.

Abstract: The fungus Macrophomina phaseolina causes charcoal rot disease (CRD) in cotton, whose symptoms develop in the late stages of growth and result in wilting and death. Despite significant research efforts to reduce disease incidences, effective control strategies against M. phaseolina are an ongoing scientific effort. Today’s CRD control tends toward green options to reduce the chemicals’ environmental footprint and health risks. Here, different Trichoderma species were examined separately and in combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…The current study intended to establish an integrated control method to protect cotton plants against charcoal rot pathogen using selected Trichoderma fungal strains, which demonstrated success in lab and seedlings tests [30] and entire season trials [9], and a previously successfully tested systemic chemical fungicide, Azoxystrobin [9]. Our prior research confirmed the tolerance of the Trichoderma species to Azoxystrobin, even at relatively high compound concentrations [33].…”
Section: Introductionmentioning
confidence: 63%
See 4 more Smart Citations
“…The current study intended to establish an integrated control method to protect cotton plants against charcoal rot pathogen using selected Trichoderma fungal strains, which demonstrated success in lab and seedlings tests [30] and entire season trials [9], and a previously successfully tested systemic chemical fungicide, Azoxystrobin [9]. Our prior research confirmed the tolerance of the Trichoderma species to Azoxystrobin, even at relatively high compound concentrations [33].…”
Section: Introductionmentioning
confidence: 63%
“…The pathogen typically enters the roots by exploiting cracks in the phelloderm, resulting from dense soils' expansion and cracking in hot, dry weather [4]. Preceding the irrigation timing can result in better growth, yield, and health than late spring watering [9]. The fungal uses cell-wall-degrading enzymes to penetrate and kill the host plant cells [10].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations